Narrow width of muscle-preserving selective laminectomy demonstrated sufficient surgical outcomes and reduced surgical invasiveness. (June 2018) - Nori, Satoshi; Shiraishi, Tateru; Aoyama, Ryoma; Ninomiya, Ken; Yamane, Junichi; Kitamura, Kazuya; Ueda, Seiji
Highlights: Sufficient functional recovery can be achieved using narrow selective laminectomy. Narrow selective laminectomy reduces surgical invasiveness and C5 palsy incidence. Wide decompression is not always necessary for cervical compressive myelopathy. Abstract: Sufficient width of laminectomy or laminoplasty is considered a criterion for successful surgical outcomes following posterior cervical decompression. No previous study has focused on surgical outcomes achieved by wide versus narrow decompression. This study examined whether narrow laminectomy width (LW) affected surgical outcomes in cervical compressive myelopathy (CCM). Between 2005 and 2010, we performed muscle-preserving selective laminectomy (SL) with decompression between the bilateral medial margin of the facet joints (wide SL). After 2010, we began to perform narrow SL, in which the LW was no more than 2–3 mm wider than the spinal cord width (SW). Clinical features and radiological findings from 97 CCM patients in whom SL was performed at two consecutive levels, including the C4/5 level, were examined in this study. The relationship between LW and patients' functional outcomes was analyzed. Mean blood loss was lower in the narrow SL group than in the wide SL group. The length of hospital stay was also shorter in the narrow SL group. The wide SL group showed greater posterior spinal cord shift. The incidence of C5 palsy correlated with LW and LW minus SW (LW-SW). The recovery rate (RR) of Japanese Orthopaedic Association score was comparable between the two groups. The RR was not correlated with LW and LW-SW. Sufficient functional recovery can be achieved by narrow SL, and it offers advantages over wide posterior decompression, including reduced surgical invasiveness and complications. Wide decompression width is not always necessary for CCM patients.